THE PROCEDURE OF STRUCTURING THE CHAPTER IN THE NOVEL OF MILOS BLACK (Heritage, 2020)
The subject of research in this work are the actions which helped Milos Crnjanski to structure and form the titles of the chapters in the novel „Seobe I“. Personal acts have resulted in unusual and different constructions comparing to the former art expression, which syntax in prose brings closer to syntax in poetry and on that way they become the characteristic of the writer’s style.  By appearance not connected segments of a text are connected on the other way, which is so specific only for this writer. Therefore there is a need for a research of those separated, but in the same time so connected segments of a text in which the essence of understanding is hidden. Repetition, inversion, division, connection and variation in title structure create on one side, special dynamic and by appearance independent parts, while, on the other hand, make coordinated and tight connected entirety. Unique and typically made sentence constructions have been analyzed on a concrete literally artistic corpus by methods of analysis, synthesis and description, with syntax, semantics and stylistics criteria. Because of clear structure and the role in understanding the discourse in general, it was necessary to involve textual criteria, as well, just to show (in)dependence of title structure from their sense and connection with a context, which makes the text of the novel.
Keywords: titles, title structure, inversion, division, repetition, connection, novel „Seobe I“, Milos Crnjanski